2015
DOI: 10.1037/a0039811
|View full text |Cite
|
Sign up to set email alerts
|

Exploring play therapy training: An investigation on the impact of practice on attitudes, knowledge, and skills with master’s level students.

Abstract: Using a quantitative approach, the researchers examined the impact of child-centered play therapy (CCPT) training and in vivo experiences on graduate students' play therapy attitudes, knowledge, and skills. Thirteen master's level students participated in the study. A repeated measure ANOVA was used to measure the impact training and in vivo experiences had on the revised Play Therapy Attitude-Knowledge-Skills Survey. From pretest to posttest (training), there were statistically significant improvement and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 22 publications
5
26
0
Order By: Relevance
“…In terms of differences among new and more experienced students, experienced students scored their skills higher at the beginning of the semester while newer students scored their play therapy skills higher than the experienced students at the end of the semester. We believe these results mirror the critical period described in the Muro et al (2015) investigation on graduatelevel, advanced play therapy students. In their investigation, Muro et al (2015) found that play therapy students undergo a critical period where skills grow during training, but decrease after training sessions.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In terms of differences among new and more experienced students, experienced students scored their skills higher at the beginning of the semester while newer students scored their play therapy skills higher than the experienced students at the end of the semester. We believe these results mirror the critical period described in the Muro et al (2015) investigation on graduatelevel, advanced play therapy students. In their investigation, Muro et al (2015) found that play therapy students undergo a critical period where skills grow during training, but decrease after training sessions.…”
Section: Discussionsupporting
confidence: 77%
“…Further, this investigation demonstrated that an introductory play therapy course positively impacts not only graduate students' knowledge about play therapy but also increases their awareness and attitudes regarding children and themselves. Muro et al (2015) investigated a two-phase training model which consisted of play therapy training sessions (Phase 1) as well as a servicelearning project conducting play therapy sessions at an elementary school (Phase 2) within a semester-long graduate-level course. Results from pretest to posttest showed a statistically significant increase in students' attitudes, knowledge, and skills.…”
Section: University-based Play Therapy Trainingmentioning
confidence: 99%
“…Students' scores were significantly different between the pretest and the first posttest in all three subscales. In the second posttest, there were significant changes in the students' scores in the knowledge and attitudes subscales (Muro et al, 2015).…”
Section: The Ptakss and Mixed-methods Play Therapymentioning
confidence: 94%
“…The instrument was designed to measure the respondent's beliefs and patterns of interaction in CCPT and their knowledge of CCPT and to assess their confidence in their play therapy skills (Crane & Brown, 2003). After being used in Taiwan to study play therapy, the PTAKSS was updated in 2007, resulting in a reduced number of items to enhance construct clarity (Kao & Chang, 2007;Muro et al, 2015. This revision was shown to have high internal consistency (⍺ = .95) and solid split-half reliability (r ¼ = .76), with three factors revealed in the factor analysis, accounting for 47.6% of variance of the scale scores (Kao & Landreth, 2007;Lindo et al, 2016. The PTAKSS has been used to study play therapy coursework with both undergraduate and graduate counseling students (Carnes-Holt & Weatherford, 2013;Homeyer & Rae, 1998;Kagan & Landreth, 2009;Lindo et al, 2016Pereira & Smith-Adcock, 2013.…”
Section: The Ptakss and Mixed-methods Play Therapymentioning
confidence: 99%
See 1 more Smart Citation